Development and Evaluation of Bullocks Drawn Multipurpose Tool Carrier Suitable for the Eastern Plateau - Gautam, Anand; Jogdand, S. V.; Patel, Bharat (Prabandhan: Indian Journal of Management, 2015)
The Multipurpose Tool Carrier (MPT) was developed to prepare the seed bed in dry and wet soil conditions and to perform various other agricultural operations. Various field operations can be performed with the help of the multipurpose tool carrier (MPT) with minimum investments of time and money. The average field capacity of the attachments, that is, cultivator (with shovel and sweep) and seed drill for dry field were found to be 0.1385, 0.1263, and 0.1758 ha/h. It gave higher field capacity (1 ha/day) with additional savings in the cost of operation. The operational cost of MPT cultivator (with shovel and sweep) and seed drill were found to be 551.54, 415.83, and 622.97 Rs /ha respectively in comparison to the Tendua plough. It was observed that the use of MPT is much economical than the traditional methods. The fabrication cost of MPT with attachments (cultivator with shovel, sweep, and seed drill) was about Rs 8000.